A year in the life of the Eastern Mediterranean: Monthly dynamics of phytoplankton and bacterioplankton in an ultra-oligotrophic sea. (April 2022) - Reich, Tom; Ben-Ezra, Tal; Belkin, Natalya; Tsemel, Anat; Aharonovich, Dikla; Roth-Rosenberg, Dalit; Givati, Shira; Bialik, M.; Herut, Barak; Berman-Frank, Ilana; Frada, Miguel; Krom, Michael D.; et al.
Abstract: The Eastern Mediterranean Sea (EMS) is a poorly studied ultra-oligotrophic marine environment, dominated by small-size phyto- and bacterioplankton. Here, we describe the dynamics of a single annual cycle (2018–19) of phyto- and bacterioplankton (abundances, pigments and productivity) in relation to the physical and chemical conditions in the photic water column at an offshore EMS site (Station THEMO-2, ∼1, 500 m depth, 50 km offshore). We show that phytoplankton biomass (as chlorophyll a ), primary and bacterial productivity differed between the mixed winter (January–April) and the thermally stratified (May–December) periods. Prochlorococcus and Synechococcus numerically dominated the picophytoplankton populations, with each clade revealing different temporal and depth changes indicative to them, while pico-eukaryotes (primarily haptophytes) were less abundant, yet likely contributed significant biomass. Estimated primary productivity (∼32 gC m −2 y −1 ) was lower compared with other well-studied oligotrophic locations, including the north Atlantic and Pacific (BATS and HOT observatories), the western Mediterranean (DYFAMED observatory) and the Red Sea, and was on-par with the ultra-oligotrophic South Pacific Gyre. In contrast, integrated bacterial production (∼11 gC m −2 y −1 ) was similar to other oligotrophic locations. Phytoplankton seasonal dynamics were similar to those at BATS and the Red Sea, suggesting an observable effect of winter mixing in this ultra-oligotrophic location. These results highlight the ultra-oligotrophic conditions in the EMS and provide, for the first time in this region, a full-year baseline and context to ocean observatories in the region. Highlights: Bacterioplankton dynamics were assessed monthly in the Eastern Mediterranean Sea. Small-sized picophytoplankton numerically dominated the phytoplankton community. Seasonal phytoplankton dynamics are similar to BATS and Red Sea, but not to HOT. Annual primary productivity is among the lowest in the world's oceans. Bacterial to primary production ratio is higher than most oligotrophic seas.